A fresh scientific look at transfer and persistence: From a materials science and tribology perspective. Issue 1 (9th August 2021) - Aberle, Michael G.; Kobus, Hilton; Robertson, James; O'Driscoll, Caroline; Hoogewerff, Jurian A.
Abstract: Knowledge of the mechanisms governing transfer, persistence, and recovery of trace evidence, together with background prevalence in the population of interest, and other task relevant information, is key for the forensic interpretation and reconstruction of what happened at the activity level. Up to now, this informational "toolkit" has largely been developed through empirical forensic studies on specific trace materials such as glass, textile fibers, and soil. Combined with the identified systemic siloing between disciplines, while valuable, such research tends to be very material‐dependent, introducing specific parameters and interpretations that may have actually impeded the recognition of underlying foundational factors applicable to most material types. In Australia, there has been a renewed interest in developing a discipline‐independent framework for the interpretation and/or reconstruction of trace evidence to interpret specific circumstances in casework. In this paper, we present a discipline agnostic "way of thinking" that has been anchored in foundational science underpinning the trace evidence discipline. Physical and mechanical material properties such as material geometry and surface topography, strength, stiffness, and hardness collectively influence contact interactions through underlying friction, wear, and lubrication cause and effect mechanisms. We discuss how these fundamental factors and parameters stemming from materials science and tribology may be adopted and adapted by forensic practitioners and researchers to contribute to a better understanding of transfer, persistence, and recovery mechanisms irrespective of evidence discipline and material type. Examples are provided to demonstrate the practical significance to real‐life casework and academic research.